Thinking about need - Alexander Max Bauer; Adele Diederich; Stefan Traub; Arne R. Weiss (The Journal of Economic Inequality, 2025)
We examine the role of need satisfaction in non-comparative justice ratings of endowments with goods. As normative approaches, we discuss utilitarianism, prioritarianism, and three versions of sufficientarianism. Using a vignette experiment with 109 participants, we elicit the participants' justice ratings of endowments with living space and estimate their justice evaluation functions. We show that a need context increases the prevalence of prioritarianistic and sufficientarianistic justice ratings. Moreover, a need threshold also changes the utilitarians' justice evaluation functions significantly.
Keywords: 300; Basic Needs; Justice Principles; Prioritarianism; Sufficientarianism; Utilitarianism; Vignette Experiment